1999
DOI: 10.1046/j.1365-2958.1999.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

A response regulator‐like protein that functions at an intermediate stage of sporulation in Streptomyces coelicolor A3(2)

Abstract: SummarywhiI is one of several loci originally described as essential for sporulation in Streptomyces coelicolor A3(2). We have characterized whiI at the molecular level. It encodes an atypical member of the response regulator family of proteins, lacking at least two of the residues strongly conserved in the conventional phosphorylation pocket. It is not adjacent to a potential sensor kinase gene. Fifteen mutant alleles of whiI were sequenced, revealing, among others, six mutations affecting conserved amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 44 publications
4
96
0
Order By: Relevance
“…The high precision of the recombination occurring between 39-bp sequences was more extensively documented in experiments with another gene, whiI (28). Cosmid DNA samples from 50 transformants were all shown to contain the desired gene replacement both by restriction analysis and by PCR, using primers annealing 100 bp outside the 39-bp tail sequences.…”
Section: Resultsmentioning
confidence: 98%
“…The high precision of the recombination occurring between 39-bp sequences was more extensively documented in experiments with another gene, whiI (28). Cosmid DNA samples from 50 transformants were all shown to contain the desired gene replacement both by restriction analysis and by PCR, using primers annealing 100 bp outside the 39-bp tail sequences.…”
Section: Resultsmentioning
confidence: 98%
“…The complex early whi mutant phenotypes suggest that some or all of the six "early" whi genes encode regulatory elements. Indeed, whiG encodes a sigma factor ( WhiG [11,37]), whiH encodes a repressor-like protein (31), and whiI encodes a response regulator-like protein (1); the product of whiB has features that resemble those of some transcription factors (13,34). Mutations in some other more recently discovered genes also affect sporulation septation but in a more allele-specific manner (30).…”
mentioning
confidence: 99%
“…whiA and whiB are therefore believed to play a role in the cessation of aerial growth. Flärdh et al (15) and Aínsa et al (1) proposed that this is part of a hypothetical sequentially dependent series of developmental decisions. In this model, newly emerged aerial hyphae first switch to a sporulation-specific mode of elongation through the action of WhiG , eventually undergoing a WhiA-and WhiBdependent orderly cessation of elongation and DNA replication, presumably in response to some signal(s); it is suggested that growth cessation then sets off further signals, which activate the WhiH and WhiI proteins, and the activated forms of these proteins switch on sporulation septation.…”
mentioning
confidence: 99%
“…The expression of glgBII therefore depends on whiG, but not on whiH or I (both of which are themselves directly and completely whiG-dependent; Ryding et al, 1998;Aínsa et al, 2000) or whiA or B (which are whiG-independent; Aínsa et al, 1999). The abundance of aerial-mycelium-associated glycogen in whiG mutants may reflect the absence of WhiH from such mutants, if WhiH does indeed influence the quantity of glycogen in aerial hyphae (see above).…”
Section: Discussionmentioning
confidence: 98%
“…Mutants in the remaining well-studied early whi genes display at least some coiling of aerial hyphal tips (Chater et al, 1989;Flärdh et al, 1999). Among theses genes, whiA encodes a protein of unknown function with orthologues in several other Gram-positive bacteria (Aínsa et al, 2000); whiB belongs to a gene group whose products code for actinomycete-specific small cysteine-rich regulatory proteins of unknown structure (Davis & Chater, 1992;Soliveri et al, 2000); whiH encodes a member of the GntR family of transcription factors (Ryding et al, 1998); and whiI encodes an atypical member of the kind of response regulator usually associated with histidine protein kinases in bacterial two-component systems (Aínsa et al, 1999). Both whiH and whiI are direct targets for RNA polymerase holoenzyme containing s WhiG (Ryding et al, 1998;Aínsa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%